Penggilingan Padi Mobile Untuk Meningkatkan Pendapatan Usaha Kecil - A. St Fatmawaty; A Arif Bijaksana (JSSHA ADPERTISI JOURNAL, 2022)
One of the efforts to maintain the availability of rice is the availability of easily accessible rice milling equipment, such as the mobile rice mill model. The mobile rice mill business can make it easier for farmers in terms of shorter time and no longer need to pay for transportation costs and can be run with profit sharing from the amount of milled grain. This mobile rice mill business started in 1980 and is still used today, so it is necessary to study the feasibility of this mobile rice mill business to increase the income of small business farmers. The research was conducted in Manisa Village, Baranti District, Sidrap Regency in February-March 2022. The data collection techniques used were interviews, observation, documentation and used data analysis in the form of NPV, Net B/C Ratio, Gross B/C Ratio, and Profitability Ratio. The results showed that 1) The non-financial aspects of the mobile rice mill business include market aspects that are acceptable to the market. 2) The investment and operational costs of mobile rice milling businesses increase every year according to annual needs. 3) The income earned at mobile rice mills averages IDR 419,156,400/year. 4) Based on the financial aspect of the mobile rice mill business with a total of Rp. 463,674,829.03> 0, then the rice milling business is feasible to run.